Capacitively Coupled Instrumentation amplifier with optimized feedback pseudo-resistor for wet-gel based electrodes. (2020) - Gupta, Lipika; Kumar, Amod; Singh, Sartajvir
Abstract: Different types of electrodes are used for stable monitoring of physiological signals. Commonly used Silver-silver chloride (Ag/AgCl) metal gel-based electrodes and gold metal electrodes used for ECG and EEG respectively introduce substantial noise component and offer very high contact impedance to the subsequent amplifier. A Capacitively Coupled Instrumentation Amplifier (CCIA) is extensively used for low noise amplification of the acquired bio-potential signal. Amplification of low-frequency bio-potential signals while discarding the DC-offset requires a distinct low-frequency high-pass pole, which is implemented using pseudo-resistors in feedback of CCIA. However, pseudo-resistors exhibit the non-linearity due to large voltage swing at the output. This also makes the high-pass pole of the system time-variable. In this paper, different structures of non-tunable and tunable pseudo-resistor are simulated using Cadence spectre simulator with 0.18 µm technology. The structures having equivalent resistance ∼1 TΩ over ±1 V range are the employed across the feedback of current mirror based CCIA. The simulation results show the improvement in the lower cut-off frequency and performance metrics of CCIA using different pseudo-resistor structures.